Managing Coastal Risks in West Africa - World Bank Group (World Bank, Washington, DC, 2016)
Coastal erosion is a naturally occurring process that is accelerated by human impacts. Artificial stabilization of the shoreline, the deterioration of natural formations, the construction of infrastructure, the extraction of materials, and the proliferation of dams deprive fragile coastal areas of important sediment deposits, which leads to erosion. Degradation of the shoreline reduces the natural protection of coastal areas to storm surges, which, together with heavy precipitation, exposes low-lying areas to flooding. Given the trans boundary nature of the region’s ecosystems, the potential downstream effects of infrastructure, and the importance of the coastline for all sectors, optimal solutions to reduce the risk along West Africa’s coasts can be reached only through multi sectoral action and multinational cooperation. Every national and regional development plan in West Africa should take coastal risks and adaption to climate change into consideration.